The Relationship between Visceral Fat and Cognitive Function in Medical Students - Budiman, Anisa Novita; Bustamam, Nurfitri; Safira, Lisa; Makkiyah, Feda Anisah (Window of Health : Jurnal Kesehatan, 2024)
During COVID-19, there was a change in student lifestyle, which triggered visceral fat accumulation. The accumulation of visceral fat is one of the causes of systemic inflammation, which is dangerous for the integrity of the brain and can potentially reduce cognitive function. This study aimed to determine the relationship between visceral fat and cognitive function among medical students. This study used a cross-sectional design towards 73 Faculty of Medicine Universitas Pembangunan Nasional “Veteran” Jakarta students who met the criteria and were selected using a simple random sampling technique. The measurement of visceral fat was done using the Tanita Body Composition Analyzer, while the measurement of cognitive function was done using the Digit Symbol Substitution Test questionnaire. The study showed differences in sex and body mass index between normal and high visceral fat groups. There were no differences in age, consumption of junk food, and physical activity between the visceral fat groups. The Spearman test results showed a relationship between visceral fat and cognitive function (p-value equal 0.000; r equal -0.561). The higher the visceral fat, the lower the cognitive function.